Revising the Who and When of Nixon's Efforts to End the Vietnam War. - Demmer, Amanda C (Diplomatic History, 2025)
The article "Revising the Who and When of Nixon's Efforts to End the Vietnam War" discusses the scholarly neglect of the Nixon years in histories of the Vietnam War and highlights David L. Prentice's book "Unwilling to Quit," which offers a new interpretation of the end of US involvement in the war. Prentice argues that US Secretary of Defense Melvin Laird played a central role in decisions about the US exit, focusing on the strategy of Vietnamization. The book challenges existing interpretations of the war's exit, emphasizing the importance of 1969 in understanding subsequent events and questioning the "decent interval" theory.